A Maximum Efficiency Point Tracking System for Wireless Powering of Biomedical Implants. (2015) - Stoecklin, S.; Volk, T.; Yousaf, A.; Reindl, L.
Abstract: Inductive power transfer systems are widely used to supply the current generation of biomedical implants. However, the power transfer efficiency is highly dependent on both the mutual coupling of the coils and the load impedance of the implant side. To overcome the challenge of time-dependent coil orientation and load impedance changes due to different power consumption levels, a maximum efficiency point tracking (MEPT) system for inductive links is presented within this work. After characterizing the momentary mutual inductance of the transmission channel, the designed system calculates the optimum load impedance and performs a dynamic impedance matching by emulating this optimum load with an input voltage-controlled switching regulator. Therefore, the presented system is capable of extracting energy at the best case efficiency for a wide range of real loads. The implemented system features a small system size (14 x 14 mm 2 ) and a low self-consumption of only 250 μW, while providing up to 100 mW to the load.